Nietrzeźwość a ryzyko zgonu w wypadku komunikacyjnym = Insobriety and the risk of death in traffic accident - Lasota, Dorota; Staniszewska, Anna; Tarchalska-Kryńska, Bożena; Mirowska-Guzel, Dagmara; Krajewski, Paweł (Journal of Education, Health and Sport, 2015)
Lasota Dorota, Staniszewska Anna, Tarchalska-Kryńska Bożena, Mirowska-Guzel Dagmara, Krajewski Paweł. Nietrzeźwość a ryzyko zgonu w wypadku komunikacyjnym = Insobriety and the risk of death in traffic accident. Journal of Education, Health and Sport. 2015;5(6):419-432. ISSN 2391-8306. DOI 10.5281/zenodo.18926 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A419-432 https://pbn.nauka.gov.pl/works/570520 http://dx.doi.org/10.5281/zenodo.18926 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015. Nietrzeźwość a ryzyko zgonu w wypadku komunikacyjnym Insobriety and the risk of death in traffic accident Dorota Lasota1*, Anna Staniszewska1, Bożena Tarchalska-Kryńska1, Dagmara Mirowska-Guzel1, Paweł Krajewski2 1 Katedra i Zakład Farmakologii Doświadczalnej i Klinicznej Warszawskiego Uniwersytetu Medycznego 2 Zakład Medycyny Sądowej Warszawskiego Uniwersytetu Medycznego Autor do korespondencji: mgr Dorota Lasota Katedra i Zakład Farmakologii Doświadczalnej i Klinicznej WUM Banacha 1b, 02-097 Warszawa e-mail: dorota.lasota@wum.edu.pl Streszczenie Wprowadzenie. Wypadki komunikacyjne są istotnym problemem cywilizacyjnym, a także medycznym i społecznym. Ponadto są dominującą przyczyną urazów, których skutki mogą prowadzić do trwałego uszczerbku na zdrowiu, a nawet śmierci. Czynnikiem w sposób istotny wpływającym na wzrost ryzyka wypadków komunikacyjnych jest nietrzeźwość. Cel pracy. Analiza stanu trzeźwości i jej wpływu na śmiertelność ofiar wypadków komunikacyjnych. Materiał i metoda. Dane uzyskano z Zakładu Medycyny Sądowej Warszawskiego Uniwersytetu Medycznego. Analizą objęto dane z lat 2009-2013. Grupę badaną stanowiły ofiary wypadków komunikacyjnych. W analizie uwzględniono wiek, płeć, wyjściową przyczynę zgonu, wynik badania sekcyjnego oraz stężenie alkoholu etylowego w materiale biologicznym. Wyniki. Liczba ofiar wypadków komunikacyjnych w badanym czasie miała tendencję malejącą. Najliczniejszą grupę ofiar wypadków komunikacyjnych spośród wszystkich kategorii stanowili piesi. U nietrzeźwych pieszych, odnotowano istotnie wyższe stężenia alkoholu w porównaniu do innych nietrzeźwych ofiar wypadków komunikacyjnych. W analizowanym materiale stwierdzono ponadto zależność między stężeniem alkoholu a wiekiem i płcią nietrzeźwych ofiar wypadków komunikacyjnych. Wnioski. Nietrzeźwość uczestników ruchu drogowego to jeden z najistotniejszych czynników ryzyka wypadków komunikacyjnych ze skutkiem śmiertelnym. Wiele uwagi poświęca się nietrzeźwości kierowców, tymczasem równie istotnym problemem okazuje się być nietrzeźwość pieszych, na co wskazują wyniki przeprowadzonej analizy. Nie tylko więc nietrzeźwi kierowcy, ale również nietrzeźwi piesi stwarzają potencjalne ryzyko wypadku komunikacyjnego. Nietrzeźwość wydaje się być dużym problemem wśród mężczyzn, stanowiących znaczącą liczbę ofiar wypadków komunikacyjnych. Słowa kluczowe: uraz wielonarządowy, obrażenia wielonarządowe, alkohol etylowy, etanol, wypadek komunikacyjny. Summary Introduction. Traffic accidents are one of the biggest problems of civilization. It also has a large medical and social problem. Traffic accidents are the dominant cause of injury, the effects of which can lead to permanent health damage and even death. Another factor significantly influencing the increased risk of traffic accidents is insobriety. Aim of the study. Analysis of sobriety and its impact on mortality of victims of traffic accidents. Material and methods. Data were obtained from the Department of Forensic Medicine, Medical University of Warsaw. The analysis included data for the years 2009-2013. Group were subjected to analysis of traffic accident victims. The analysis included age, sex, initial cause of death, the result section, and the concentration of ethyl alcohol in biological material. Results. The number of victims of traffic accidents was considered short span downward trend. However, the largest group of victims of traffic accidents among all categories were pedestrians. It is in intoxicated pedestrians, reported significantly higher levels of alcohol compared to other intoxicated victims of traffic accidents. In the analyzed material it was also found between the concentration of alcohol dependence and the age of intoxicated victims of traffic accidents - the older the victim, the higher the alcohol concentration and a significantly higher concentration of alcohol in drunken intoxicated men than in women. Conclusions. Drunkenness road is one of the most important risk factors of traffic accidents with fatalities. We talk a lot about the intoxication of drivers, while equally important problem turns out to be drunken pedestrians, as shown by the results of the analysis. Thus, not only drunk drivers, but also intoxicated pedestrians pose a high risk of a traffic accident. Insobriety seems to be a big problem among men, accounting for a significant number of victims of traffic accidents. Key words: polytrauma, multi-organ damage, ethyl alcohol, ethanol, traffic accident.